Environmental monitoring at a former uranium milling site : pollution by radionuclides at tailing ponds of Koshkar-Ata, Kazakhstan /: pollution by radionuclides at tailing ponds of Koshkar-Ata, Kazakhstan. (2018) - Kuterbekov, Kairat
No abstract available